Physiochemical and Pharmaceutical Properties of Guar Gum Derivatives - Najaf Iqbal, Dure; Akbar Hussain, Erum (Asian Journal of Chemistry, 2010)
Despite the vast importance of green chemistry synthesis and characterization of environmental friendly modified natural polymers is the need of time. These natural polysaccharides eliminate the danger to health and environment. Guar gum is one of the important naturally occurring polymer which has wide applications due to its rheological modifying properties in medicinal, pharmaceutical, food, textile and scores of other industrial and commercial sectors. There has been wide study on physiochemical and pharmaceutical properties of guar gum. But study on modified guar gum and its derivatives is quite lacking. The unmodified guar gum has certain drawbacks like lack of clarity and free flowing properties, fall in viscosity and turbidity on prolonged stay etc. These draw backs can be overcome by modifying and derivatization of guar gum and can be used in multidiscipline fields. In this review article the authors have summarized different physiochemical and pharmaceutical properties of guar gum and its derivatives.